Current Status of Loquat (Eriobotrya Japonica Lindl.): Bioactive Functions, Preservation Approaches, and Processed Products. (1st November 2022) - Dhiman, Atul; Suhag, Rajat; Thakur, Dhruv; Gupta, Viresh; Prabhakar, Pramod K
ABSTRACT: Loquat ( Eriobotrya japonica Lindl.) is a subtropical evergreen horticultural product of which E. japonica variety is used for the production of fruits and E. deflexa and E. prinoides are used for rootstocks. A good-quality loquat fruit has total soluble solids content of more than 12%, acidity in the range of 0.3–0.6% and low flesh firmness. Loquat fruit and leaves have high concentrations of vitamin A, ascorbic acid, calcium, iron, manganese, potassium, and pharmacologically active constituents such as kaempferol, ursolic acid, oleanolic acid, tartaric acid, and quercetin. It also possesses several pharmacological properties like anti-inflammatory, antitumor, antioxidative, antimutagenic, antidiabetic activity, etc. The fruit has a short shelf life and is highly susceptible to various physiological disorders and decay after harvesting. It requires proper storage techniques and post-harvest treatments (physical, chemical, and biological). To increase the availability to consumers and add more value to loquat fruit, it is processed into different products such as jam, jellies, juice, wine, canned fruit, dried slices, etc. Dried leaves can be incorporated in the development of food products such as tofu, cookies, and noodles. The loquat seeds can be used for preparing starch and extraction of oil. In view of this information, this paper is uniquely worked upon to review all discussions from past literatures along with the recent developments for understanding the paradigm of loquat and making it easy for readers and researchers to have a quick glance over recent trends and innovations. Abbreviations : TSS, total soluble solids; TPC, total phenolic content; LDL, low-density lipoprotein; HCA, hydrocinnamic acid; DPPH, 2, 2-Diphenyl-1-picryldrazyl; PPO, polyphenol oxidase; CA, controlled atmosphere; MAP, modified atmosphere packaging; POD, peroxidase; MeJA, methyl jasmonate; 1-MCP, 1-methylcyclopropene; LOX, lipoxygenase; NO, nitric oxide; ROS, reactive oxygen species; LLP, loquat leaf powder; RWD, refractance window drying; LTC, low-temperature conditioning